Childhood preoperative anxiolysis: Is sedation and distraction better than either alone? A prospective randomized study. Issue 8 (16th June 2017) - Sola, Chrystelle; Lefauconnier, Audrey; Bringuier, Sophie; Raux, Olivier; Capdevila, Xavier; Dadure, Christophe
Summary: Background: Preoperative anxiety management receives special attention in pediatric anesthesia. Different pharmacological and nonpharmacological techniques can be employed. This study was designed to assess three different strategies for childhood preoperative anxiolysis: midazolam premedication, midazolam in combination with portable Digital Video‐Disk player, or video distraction strategy alone. Methods: In this prospective randomized study, children aged 2‐12 years were assigned to one of the three study groups. The primary outcome was a change in preoperative children's anxiety, from baseline (before transfer to the preanesthetic holding area) to separation from parents, assessed by the Modified Yale Preoperative Anxiety Scale (mYPAS) and the Visual Analog Anxiety Scale (VAS‐Anxiety). Delirium emergence, postoperative pain, and parental satisfaction were also collected. Results: One hundred and thirty‐five patients were enrolled. The three preventive strategies allowed control of preoperative distress. Within the three study groups, no significant change was objectified in the anxiety level from baseline to separation from parents (mean change in mYPAS midazolam group: 2.4 95% CI [−1.7 to 6.3]; midazolam+Digital Video‐Disk group: −1.0 95% CI [−5.9 to 3]; and Digital Video‐Disk group: 1.4 95% CI [−4 to 6.7]). Comparison of change in preoperative children's anxiety between the groups did not show any difference. Emergence delirium, postoperative pain scores, and analgesic consumption were similar between the groups and parents' satisfaction was excellent. Conclusion: Both pharmacological premedication and video distraction are effective strategies for controlling preoperative childhood anxiety. The combination of midazolam and Digital Video‐Disk player was not better than either alone.